2020
DOI: 10.1111/1467-8268.12475
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factors affecting nonperforming loans in commercial banks: The case of African lower middle‐income countries

Abstract: A nonperforming loan refers to a loan that is not paid as and when due, and it is a significant issue that banks need to keenly consider for them to exist and be stable. There are several factors accountable for nonperforming loans; some are firm-specific, while others are macroeconomic factors. The study of banking sector stability is a foundation of modern macroeconomic policy of a bank-based economy. In this view, this study aims to investigate the determining factors from both perspectives. This study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…The Capital Adequacy Ratio (CAR), measures the degree of banks' solvency, stability, soundness as well as their ability to absorb risk. According to some studies [9,11], CAR is negatively related to NPL; Olarewaju [12] reported that, capital adequacy has a significant and indirect impact on the NPLs of the banks in Low Middle Income (LMI) economies. This means an increase in CAR will enable banks to keep more funds aside to meet liabilities and other obligations hence reducing the number of initial loans and resultant NPLs.…”
Section: Bank Specific Variablesmentioning
confidence: 99%
“…The Capital Adequacy Ratio (CAR), measures the degree of banks' solvency, stability, soundness as well as their ability to absorb risk. According to some studies [9,11], CAR is negatively related to NPL; Olarewaju [12] reported that, capital adequacy has a significant and indirect impact on the NPLs of the banks in Low Middle Income (LMI) economies. This means an increase in CAR will enable banks to keep more funds aside to meet liabilities and other obligations hence reducing the number of initial loans and resultant NPLs.…”
Section: Bank Specific Variablesmentioning
confidence: 99%
“…Liquidity management, on the other hand, has a negative impact on banks' financial performance. The significant factors affecting nonperforming loans in the banking sector of lower middle-income countries, according to Olarewaju (2020), were lagged nonperforming loans, lending rate, capital adequacy, credit growth, cost income ratio and real interest rate. In addition, Amano (2014) studied the determinants of Ethiopian CB lending behavior such as bank size, deposit ratio, liquidity ratio, interest rate and reserve requirement, real GDP rate and inflation rate.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…En revanche, les petites banques, sont exposées au problème de sélection adverse en raison du manque de compétences et d'expériences nécessaires pour évaluer efficacement la qualité des crédits. Utilisant la méthode des moments généralisés sur 110 banques commerciales, Olarewaju (2020) montre que le cout du crédit et l'adéquation du capital influencent les PNP dans les pays à revenu intermédiaire.…”
Section: Revue De La Littératureunclassified
“…Plusieurs travaux empiriques ont montré que les facteurs microéconomiques propres aux banques tels que la taille de l'institution, les marges de profit, l'efficacité et l'efficience managériale, la rentabilité, les conditions de crédit, le profil de risque, et le pouvoir de marché sont des déterminants majeurs des prêts non performants (Louzis et al, 2012; Olarewaju, 2020).…”
Section: Revue De La Littératureunclassified